Application of sustainable materials in the hardscape elements of parks - Jamaluddin, Adam; Abu Bakar, Aniza (Kulliyyah of Architecture and Environmental Design, International Islamic University Malaysia, 2017)
Green spaces are much needed in the urban environment for a multitude of reasons. One of them is to curb environmental problems such as flash flood, urban heat island and to increase the quality of life of the users. However, sometimes the parks that are supposed to help in improving the environment may have no significant effects or they might even harm the surrounding due to the unsuitable materials used. This research focuses on finding out the park’s level of sustainability in terms of the hardscape elements used based on its sources and how they affect the environment. One of the ways to bring out the optimum potential of parks is to incorporate sustainable hardscape elements in them. Appropriate materials selection could tackle natural phenomenon such as heavy rain as the water runoff can be reduced. This study is carried out by conducting a site investigation at Taman Tasik Dato’ Keramat on its current hardscape elements, followed by the identification of the potential to replace the hardscape elements with sustainable materials to increase the park’s environmental sustainability. It is found that swapping out materials can increase the park’s level of sustainability quite significantly.